Status-Encycle of Our National Music+ - Topildiyev Saidmurod Odiljon oglu (Zien Journals, 2021)
“About 300 participants and guests from 73 countries of the world are taking part in this art festival, which is being held in our country for the first time. We are very pleased to have among them famous singers and musicians, cultural and artistic figures, musicologists, not only in their own country, but also around the world,” the President said in his speech.
Keywords: archeology; spiritual heritage; tradition; Internet